Sleep Preferentially Enhances Memory for Emotional Components of Scenes - Payne, Jessica D.; Stickgold, Robert; Swanberg, Kelley; Kensinger, Elizabeth A. (Psychological Science, 2008)
Central aspects of emotional experiences are often well remembered at the expense of background details. Previous studies of such memory trade-offs have focused on memory after brief delays, but little is known about how these components of emotional memories change over time. We investigated the evolution of memory for negative scenes across 30 min, 12 daytime hours spent awake, and 12 nighttime hours including sleep. After 30 min, negative objects were well remembered at the expense of information about their backgrounds. Time spent awake led to forgetting of the entire negative scene, with memories of objects and their backgrounds decaying at similar rates. Sleep, in contrast, led to a preservation of memories of negative objects, but not their backgrounds, a result suggesting that the two components undergo differential processing during sleep. Memory for a negative scene develops differentially across time delays containing sleep and wake, with sleep selectively consolidating those aspects of memory that are of greatest value to the organism.